A Hybrid Islanding Detection Method For Distribution Systems - Pouryekta A.; Ramachandaramurthy V.K. (Taylor and Francis Inc., 2023)
Continuous operation of Renewable Energy Systems (RES) is achieved either in grid-connected mode or in autonomous mode in the form of Islands or Microgrid, which has predefined boundaries. Thus, distribution systems should be capable of detecting islanding condition for smooth transition to an Islanded mode. In this article, a hybrid islanding detection method, which combines remote and passive methods, is proposed. Distributed Generation (DG) units can be in the form of inverter interfaced or synchronous based generators and when used together can cause difficulties in islanding detection such as delay or inaccurate detection. The number of DG units in the network also affects the accuracy of islanding detection. Thus a new hybrid method, which is based on communication and passive methods, is proposed to overcome this problem. The accuracy and effectiveness of the proposed hybrid method is investigated using PSCAD software. The proposed detection method features an improvement in detection accuracy. , Copyright Association of Energy Engineers (AEE).